Cognitive impairment and gray matter volume abnormalities in silent cerebral infarction. Issue 15 (21st October 2015) - Yang, Tao; Zhang, Lan; Xiang, Mingqing; Luo, Wei; Huang, Jinbai; Li, Maokun; Xiong, Xunbo; Wang, Hua
<x xml:space="preserve">Abstract</x> To investigate the association between cognitive impairment and gray matter volume (GMV) abnormalities in silent cerebral infarction (SCI) patients, the GMV of 62 pairs of patients and well-matched healthy controls was calculated. All participants underwent a P300 test, a Montreal Cognitive Assessment (MoCA) test. Compared with controls, the patients showed decreased GMV in the left superior frontal gyrus, left inferior frontal gyrus, left superior temporal gyrus, right middle temporal gyrus, and bilateral parahippocampal gyrus; no significantly increasing GMV was found. The volumes of the frontal and temporal lobes were positively correlated with the score of the MoCA scale and P300 amplitudes (r≥0.62, P<0.01). The P300 latency was negatively correlated with the volumes of the frontal lobe, the temporal lobe, and the hippocampus (r⩽−0.71, P<0.05). No significant correlations between the GMV of the abnormal brain regions and four clinical characteristics in SCI patients were found, suggesting that cognitive deficiency existed in SCI patients and the reduced GMV might contribute to the pathology of cognitive deficiency in SCI patients